Viruses as a Trigger for autoimmune Hepatitis in susceptible Individual - AL- Obeidy, Eman Sh.; Al.Obeidy, Aswad H.; Asker, Bassim A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Autoimmune hepatitis (AIH) is a rare chronic liver disease of known etiology, characterized by hypergammaglobulinemia, characteristic auto antibodies, and a favorable response to immunosuppressive treatment.Strong circumstantial evidences denoted that there is quite long list of environmental factors such as (food additives and drugs), viruses and toxins which play an important role in precipitating this disease. Patients and Methods: the study was performed on 13 Iraqi patients with acute viral hepatitis, attending the Teaching Hospital for Gastroenterology and Liver Disease and Al-Khadymia Teaching Hospital in the period between November 2003 and July 2005. ANA, SMA and anti-LKM 1 were detected by immunoflurescent technique whereas SLA/LP Ab was detected by Euroline method. Results: the thirteen patients with acute viral hepatitis were developing AIH after 3 months.Conclusion: acute viral hepatitis is a trigger of AIH.